A Hybrid Dynamic Mesh Generation Method for Multi-Block Structured Grid (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, a hybrid dynamic mesh generation method for multi-blockstructured grid is presented based on inverse distance weighting (IDW) interpolationand transfinite interpolation (TFI). The major advantage of the algorithm is that itmaintains the effectiveness of TFI, while possessing the ability to deal with multi-blockstructured grid from the IDW method. In this approach, dynamic mesh generation ismade in two steps. At first, all domain vertexes with known deformation are selectedas sample points and IDW interpolation is applied to get the grid deformation on domainedges. Then, an arc-length-based TFI is employed to efficiently calculate the griddeformation on block faces and inside each block. The present approach can be wellapplied to both two-dimensional (2D) and three-dimensional (3D) problems. The proposedmethod has been well-validated by several test cases. Numerical results showthat dynamic meshes with high quality can be generated in an accurate and efficientmanner.